Isolation and characterization of Angiotensin Converting Enzyme (ACE) inhibitory compounds and antioxidant activities of Tacca integrifolia / Farah Liyana binti Jamaludin - Jamaludin, Farah Liyana (2013)
Tacca integrifolia Ker-Gawl is belongs to the family of Taccaceae and locally know as “Belimbing Tanah”. It has been used traditionally for the treatment of hypertension, hemorrhoids, heart failure and kidney disease. The thin layer chromatography (TLC) of hexane, petroleum ether, chloroform, methanol and water extract of leaves and rhizome showed the presence of phenols, flavonoids, terpenoids, essential oil and alkaloid compounds. The analysis of the leaves and rhizome extract with LCMS/MS showed that it contained proanthocyanidin, proanthocyanidin trimer, p-hydroxybenzoic acid, phenolic acid conjugate, protocatechuic acid, quinic acid and dicaffeolquinic acid conjugate. The total phenol contents w e re highest in leaves and rhizomes extract of water at 792.7mgGAE/g and 350.8mgGAE/g respectively. Whereas, the highest total flavonoids contents were highest in petroleum ether leaves extract and in chloroform rhizome extract at 376.7mgQE/g and 193.4mgQE/g respectively. The ACE inhibition activity at 100mg/ml was highest in leaves extract of water (45.5%) and in rhizome extract of methanol (53.6%). The isolated compounds label as A5, A7, A8, A9, B3, B5, B8, C3, C9, E1, E3, E4, F1, G1, G3 and G6 showed ACE inhibition more than 50%. Since the water extract showed highest ACE inhibition and because it is often used in traditional medicine for hypertension treatment, the water extracts were analyzed in vivo with SHR rats. The sub-acute toxicity test has shown that there were no mortality occurs under experimental conditions. Brine Shrimp Lethality Assay (BSLA) also has shown low toxicity at LC50 22981μg/ml for leaves extract and LC50 4378μg/ml of rhizome extract. The blood pressure of spontaneously hypertensive rats were reduced significantly (p<0.05) at 50mg/kg and 100mg/kg of water leaves extract and water rhizome extract respectively. The liver function test has indicated significant iii difference in AST except when compared 100 mg/kg water rhizome extract SHR group with control group, and significance also showed in total protein and ALT except when compared 50 mg/kg water leaves extract and 50 mg/kg Captopril compared to control normal SD rat, respectively. While sodium test in renal function test showed significance in difference. In the antioxidant DPPH assay the IC50 of methanol leaves, chloroform leaves and water leaves extract was 88μg/ml, 350μg/ml and 480μg/ml respectively. The ferric reducing power assay has showed that both hexane extract from leaves and rhizome gave high reducing activity. The metal chelating activity of the chloroform leaves extract showed the highest metal chelating activity of IC50 at 1.98mg/ml. In conclusion, water extract from leaves and rhizome of Tacca integrifolia contained active phytochemical compounds as detected in LCMS/MS that responsible in reducing blood pressure of spontaneously hypertensive rats significantly at 50mg/kg and 100mg/kg and possessed high antioxidant activity that could scavenged free radicals and prevented oxidative stress that related to hypertension. Thus, these results support and provide scientific evidence to the claimed made by traditional practitioner that used Tacca integrifolia for antihypertension treatment.